Pengaruh Penggunaan Media Papan Warna terhadap Kemampuan Mengklasifikasikan Warna bagi Anak Kelompok A di RA Darussalam - Ellisan; Abdul Kadir Jaelani; Aulia Dwi Amalina Wahab (Mataram University, 2026)
The ability to classify colors is one of the cognitive skills that should be developed in early childhood. However, learning activities at RA Darussalam still rely on conventional media, which provide limited opportunities for children to actively classify colors through meaningful learning experiences. This study aims to determine the effect of using color board media on the ability to classify colors in Group A children at RA Darussalam. This study employed a quantitative approach with a quasi-experimental method using a one-group pre-test post-test design. The research subjects were all 20 children in Group A at RA Darussalam. Data were collected through observation and tests using observation sheet instruments. Data analysis was conducted using the normality test and the paired sample t-test. The results showed that the use of color board media significantly improved children's ability to classify colors, as indicated by an increase in the mean score from 49.7 in the pre-test to 73.3 in the post-test. The normality test indicated that both pre-test and post-test data were normally distributed, with significance values of 0.200 (> 0.05). Furthermore, the paired sample t-test showed a significance value (Sig. 2-tailed) of less than 0.05, indicating that H₀ was rejected and Hₐ was accepted. The findings also revealed that the use of color board media increased children's activeness, enthusiasm, and understanding of color concepts through concrete and enjoyable learning activities.